Bone black : memories of girlhood - hooks, bell, 1952- (New York : Henry Holt and Co., 1996)
Stitching together girlhood memories with the finest threads of innocence, the author presents a powerfully intimate account of growing up in the South.
Keywords: hooks, bell, -- 1952- -- Childhood and youth; African Americans -- Biography; African American women -- Biography; Feminists -- United States -- Biography